Walker's EQUILIBRIUM: a review essay - Glenn Hueckel (Claremont McKenna College, Department of Economics, 2002)
Donald Walker has provided us with a three-volume collection of work drawn from the literature of the past half-century intended to illustrate the variations over that period in the form and substance of the economist's concept of equilibrium and, in so doing, to complement the well-known Debreu collection on General Equilibrium Theory. Like all such projects, this collection, through the act of inclusion (and, hence, exclusion), serves to delineate for the nonspecialist the range of the relevant questions, to identify points of controversy, and, by the ordering of the selected items, to reveal lines of intellectual development that otherwise might be obscured. Although this collection takes for its theme the question of equilibrium in all its dimensions, Walker's earlier broadside against contemporary general equilibrium literature in the Arrow-Debreu tradition looms over these volumes from start to finish. That is unfortunate since Walker's standard of a functioning model, exhibiting the highest possible degree of [institutional] realism serves to obscure rather than to illuminate the long-standing methodological division between those, on the one hand, for whom the concept of equilibrium is no more than a useful fiction whose meaning is conditioned upon the model under consideration and those others for whom the concept expresses an observable feature of the world in which we live. In this review essay, we develop an alternative organizational framework which permits us to more clearly reveal the methodological fault lines running through the literature sampled by Walker's selections and thereby to identify the intellectual filiations between the objections raised by Blaug, McCloskey, and other recent critics and those advanced long ago by Keynes, Kaldor, Robinson, and Hicks.
Keywords: 330